2018
DOI: 10.3390/s18072082
|View full text |Cite
|
Sign up to set email alerts
|

Recent Surface Water Extent of Lake Chad from Multispectral Sensors and GRACE

Abstract: Consistent observations of lakes and reservoirs that comprise the majority of surface freshwater globally are limited, especially in Africa where water bodies are exposed to unfavorable climatic conditions and human interactions. Publicly available satellite imagery has increased the ability to monitor water bodies of various sizes without much financial hassle. Landsat 7 and 8 images were used in this study to estimate area changes around Lake Chad. The Automated Water Extraction Index (AWEI), Normalized Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 78 publications
2
31
0
1
Order By: Relevance
“…14,000 km 2 , reported in others studies 10,12 . Similarly, recent studies 11,13 reported the minimum, maximum and average size of Lake Chad for the 2003-2016 period were only 1242 km 2 , 2231 km 2 and 1694 km 2 , respectively. These numbers are 2-3 times lower than what we report here.…”
Section: Land Surface Water Extent During the Last Two Decadesmentioning
confidence: 51%
See 1 more Smart Citation
“…14,000 km 2 , reported in others studies 10,12 . Similarly, recent studies 11,13 reported the minimum, maximum and average size of Lake Chad for the 2003-2016 period were only 1242 km 2 , 2231 km 2 and 1694 km 2 , respectively. These numbers are 2-3 times lower than what we report here.…”
Section: Land Surface Water Extent During the Last Two Decadesmentioning
confidence: 51%
“…However, these estimates were usually based on partial observations and thus provided incomplete information and increased misunderstanding of the Lake Chad hydrological cycle. Other studies only investigated the southern pool of the lake 11 , during some months in a year 12 , or only focused on groundwater 13 . Only two studies investigated in details the seasonal variations of the Lake Chad, but focusing on the previous decades, the 1980s and the 1990s 6,14 .…”
mentioning
confidence: 99%
“…Previous modeling of Arctic lake development has revealed that simulations improve by the inclusion of dynamic sub-grid scale waterbody size distributions (Avis et al, 2011;Van Huissteden et al, 2011;Langer et al, 2016). However, both mapping inventories and modeling approaches have mainly focused on lakes larger than 0.01 km 2 because of limitations associated with available satellite imagery (Verpoorter et al, 2012(Verpoorter et al, , 2014Jun et al, 2014;Paltan et al, 2015;Pekel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Marshes which are mostly found around the transition areas between water and sand dunes, covers about 15% of this area. Open water makes up the remaining 10% [24].…”
Section: General Overviewmentioning
confidence: 99%
“…Following the Lake Chad's drastic decrease in water levels, numerous studies have been carried out on the hydrology of the Lake Chad Basin (LCB). With the lack of in situ observations in this area, most of the studies relied on various satellite products to document hydrological changes [24,25]. Some researchers used satellite products to analyze precipitation trends and its effects on lake levels in Komadugu-Yobe which is a river that flows into Lake Chad through Nigeria and Niger [26,27].…”
Section: Introductionmentioning
confidence: 99%